Switching Mechanisms in Hybrid Job Design: A Case Study of a CEO in an Indonesian Household Equipment Manufacturing Company - Dewa Putu Yohanes Agata L. Sandopart (CV. Global Cendekia Inti, 2026)
This study aims to explore in depth the switching mechanisms implemented by a CEO of an Indonesian household equipment manufacturing company to balance the competing demands of standardization and flexibility in job design. A qualitative approach with an instrumental single-case study design was employed. Data were collected through in-depth interviews with the CEO, limited participant observation on the production floor over three days, and analysis of corporate documents. Data analysis utilized the Interpretative Phenomenological Analysis (IPA) framework. The research identified three primary switching mechanisms implemented: (1) a daily mode-switching protocol based on production line status, (2) a trigger-based escalation matrix for handling deviations, and (3) a post-mortem learning loop that integrates experiential learning into procedural updates. Findings indicate that successful switching implementation is critically dependent on systematic investment in developing worker capacity through cross-skilling and fostering a culture of psychological safety. The novelty of this research lies in being the first empirical study to document in detail the implementation of switching mechanisms within hybrid job design in the Indonesian manufacturing context.